A tool to guide herbicide control of serrated tussock in native grassland, informed by expert judgement. (16th August 2021) - Sinclair, Steve; Bruce, Matthew; Neil, James; Griffioen, Peter
Summary: Serrated Tussock (Nassella trichotoma) is a weed that invades native grasslands in southern Australia. It is frequently controlled using extensive and costly chemical control. We describe a tool aimed at grassland reserve managers that provides guidance about the suitability of different chemical control techniques, including knapsack, boom and aerial spraying. The tool takes the attributes of any site and predicts the suitability of each technique. The tool was built using random forests trained on a dataset of practitioner judgements. We discuss the applications and limitations of the tool.